(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Purpose - With the introduction of internet in 20th century, there was a paradigm shift of economy towards digitization. Promotion of financial inclusion and digitization has become the need of the hour for achieving inclusive growth of the economy. Therefore, the objective of the paper is to study the impact of digitization and demonetization on financial inclusion in India and also to assess the relationship between demonetization, financial inclusion and digitization.Design Methodology Approach - The study is based on facts and information collected from various government periodical publications, published articles, magazines, E- journals, RBI report, NABARD report, websites, etc.Findings- The findings of the study revealed that the digitization and demonetization both have positive and negative impact on financial inclusion. The study further concluded that after demonetization, 23.3 million new accounts were opened under Pradhan Mantri Jan Dhan Yojna. Out of which 53.6 were in urban areas and 46.4 were in rural areas. Thus, demonetization, financial inclusion and digitization are positively related, and lead to inclusive growth in the economy.